GOOD MANUFACTURING PRACTICES OF NORTHERN CEBU, PHILIPPINES FOOD CATERERS - Castro, Charena J. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2023)
Catering services is one of the livelihoods of Northern Cebu residents. This study assessed the respondents’ profile and the level of manufacturing practices and hazard analysis critical control point of food caterers at Northern Cebu Philippines. The study utilized the descriptive method of research using a researcher-made questionnaire with 30 respondents for the period of six months. Based on the descriptive method, 50% were male and 50% were female respondents consisting 305 ages 27 years old and above, 30% ranging from 24-26 years old and 20% for both 21-23 years old and 20% for 20 years old and below and monthly income of respondents. The level of good manufacturing practices especially before, during and after serving the foods were observed by the food caterers in the northern part of Cebu and rated as fully implemented. The level hazard analysis critical control point implementation during catering services were moderately implemented. Hence, crew of these food catering services need to be upgraded in terms of hazard analysis critical control point aspect.